Modified elastic solution method in solving elastoplastic problems of structure components subjected to complex loading - Bich, Dao Huy (Vietnam Journal of Mechanics, 2000)
Modified elastic solution method in the elastoplastic process theory has been proposed by the author [2] and was applied in solving some 2D and 3D elastoplastic problems of structure components subjected to complex loading. The method makes use of an algorithm in which a step is made in the loading process and iterations are carried out on this step. The performance of the method was fulfilled and the convergence of the method was considered numerically. In this paper the other performance of this method is presented and the convergence of the method is proven theoretically in the general case of a hardening body which obeys the elastoplastic process theory. The more complicated 3D problem of bodies of revolution subjected to non-axially symmetric load is investigated.